Aspectos petrológicos y geoquímicos de las rocas ultramáficas asociadas a la granodiorita precoz de Vivero (Lugo). - Galán, G. (Cuadernos de Geología Ibérica, 1981)
Ihis paper deals with the mineralogy and petrography of ultramafic and mafic rocks associated with a granodiorite belonging to the calc-alcaline serie of Older Hercynian granitic rocks, near Vivero (Lugo, NW of Spain). They range from peridotites to tonalites through piroxenites, hornblendites. these rocks and the associated grani .; toid ones show a typical calc-alcaline trend. We think they could probably be formed from high PH2O basaltie magma